Patogenetic and clinical features of metabolic syndrome complicated by chronic coronary (ischemic) heart disease and type 2 diabetes mellitus - R.Ya. Dutka (Danylo Halytsky Lviv National Medical University, 2018)
Aim. To determine  the diagnostic and prognostic markers of chronic coronary heart disease and type ІІ diabetes mellitus of as  complications of metabolic syndrome on the basis of the study of hormonal indexes, lipid spectrum, and echocardiography.